2009
DOI: 10.1002/ijc.24098
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ down‐regulates NKG2D ligand expression and impairs the NKG2D‐mediated cytolysis of MHC class I‐deficient melanoma by natural killer cells

Abstract: NKG2D operates as an activating receptor on natural killer (NK) cells and costimulates the effector function of ab CD81 T cells. Ligands of NKG2D, the MHC class I chain-related (MIC) and UL16 binding protein (ULBP) molecules, are expressed on a variety of human tumors, including melanoma. Recent studies in mice demonstrated that NKG2D mediates tumor immune surveillance, suggesting that antitumor immunity in humans could be enhanced by therapeutic manipulation of NKG2D ligand (NKG2DL) expression. However, signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 53 publications
(108 reference statements)
6
80
0
1
Order By: Relevance
“…34 On the other hand, stimulation by cytokines (type I and II interferons, IL-2, IL-12, IL-15, IL-18, and transforming growth factor-b) does not affect the regulation of NKp44L (data not shown), but can induce some NKG2D ligands. 46,47 These data suggest, similar to other ligands for activating NK receptors, that NKp44L transmits a danger signal in certain pathological situations, including certain infections and cancers, to induce the lysis of target cells by activated NKp44 1 NK cells.…”
Section: Discussionmentioning
confidence: 65%
“…34 On the other hand, stimulation by cytokines (type I and II interferons, IL-2, IL-12, IL-15, IL-18, and transforming growth factor-b) does not affect the regulation of NKp44L (data not shown), but can induce some NKG2D ligands. 46,47 These data suggest, similar to other ligands for activating NK receptors, that NKp44L transmits a danger signal in certain pathological situations, including certain infections and cancers, to induce the lysis of target cells by activated NKp44 1 NK cells.…”
Section: Discussionmentioning
confidence: 65%
“…Even in the absence of vaccination, MHC-I is upregulated in an IFN-g-dependent fashion on implanted B16 tumor cells within hours, and this expression is maintained during in vivo growth (44,47). IFN-g also leads to NKG2D ligand downregulation on B16 (48). These features may protect B16 from direct NK cell cytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of chronic elevated IFN-c levels is unknown, but, if associated with impaired upregulation of MICA in response to RSV infection, could lead to impaired viral clearance. It was recently reported that in human tumour cells, concurrently with the upregulation of surface MHC class I, IFN-c downregulates the levels of surface MICA [25,26]. Interestingly, chronic obstructive pulmonary disease (COPD) is associated with an exaggerated type 1 immune cell inflammatory infiltrate [7,27].…”
Section: Ifn-c Increases Rsv-induced Il-15 Levels But Downregulates Rmentioning
confidence: 99%